Attack on Titan : before the fall. 11 - Isayama, Hajime, 1986-; Suzukaze, Ryo ([Kodansha Comics, an imprint of Kodansha USA Publishing, LLC], 2017)
"Sharle has taken matters into her own hands to recruit the reclusive Angel, the original inventor of the Device that might one day help humanity fight back against the Titans. But Angel's harrowing experiences have left him scarred, and he may need extra encouragement to rejoin the struggle. Meanwhile, Kuklo remains missing, his fate in the balance..."-- back cover.